Character of the present financial crisis in USA and its possible global consequences - Petrac-Stepanović Žaklina (Međunarodni Problemi, 2008)
The US economy is facing the first big financial crisis in the 21st century. The author points out that the current crisis is much different from the previous ones by its characteristics, causes, consequences it produces on the world economy and international financial system in particular. The problems that were noticeable in the US loan market in the second half of 2007, which have escalated into a crisis of the financial system in 2008 creating instability in the world financial markets, were mostly caused by the losses on the American real estate market. For the fact that the highly integrated world economy has enabled rapidly and easily transmission the effects of real and monetary trends, reducing, on the other hand, the countries' prospects to protect their economies and populations from their effects it is evident that the way the US manages its financial system has the exceptional significance beyond USA, too. As the increasing number of countries is facing with direct or indirect effects of the current crisis it is in the interest of all those that undertaking actions to stop further negative repercussions on their national economies and ensure global economy growth. .